Challenges and Prospects of ROI Measurement in B2B Digital Marketing: Evidence from MSMEs in Gowa Regency - Andi Mustika Amin; Andi Aryani Hardiyanti (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study explores the challenges and prospects of Return on Investment (ROI) measurement in Business-to-Business (B2B) digital marketing among Micro, Small, and Medium Enterprises (MSMEs) in Gowa Regency, Indonesia. Employing a mixed-methods approach with a convergent parallel design, the research integrates quantitative data from the Central Statistics Agency (BPS) and the Department of Cooperatives and MSMEs of Gowa with qualitative insights from interviews and focus group discussions. The quantitative results show a consistent increase in MSME growth and digital adoption between 2020 and 2024, supported by the government’s initiatives to promote financial inclusion and digital payment systems such as QRIS. However, the low rate of business formalization and uneven digital literacy hinder full participation in digital transformation. Qualitative findings reveal that most MSMEs rely on intuition rather than data-driven analysis to assess marketing performance. Key barriers include limited analytical capability, lack of structured ROI frameworks, fragmented digital systems, and dependence on informal B2B networks. Despite these constraints, emerging opportunities such as AI-based analytics, social media optimization, and government-led digitalization programs demonstrate the potential for improvement. Overall, the study concludes that while MSMEs in Gowa Regency show steady progress in digital marketing adoption, their capacity to measure ROI remains underdeveloped. Enhancing digital literacy, financial management skills, and policy support is essential to enable MSMEs to evaluate marketing effectiveness and achieve sustainable competitiveness in the B2B digital landscape.